2018
DOI: 10.1063/1.5026732
|View full text |Cite
|
Sign up to set email alerts
|

Frequency dependent polarisation switching in h-ErMnO3

Abstract: We report an electric-field poling study of the geometric-driven improper ferroelectric h-ErMnO 3 . From a detailed dielectric analysis we deduce the temperature and frequency dependent range for which single-crystalline h-ErMnO 3 exhibits purely intrinsic dielectric behaviour, i.e., free from extrinsic so-called Maxwell-Wagner polarisations that arise, for example, from surface barrier layers. In this regime ferroelectric hysteresis loops as function of frequency, temperature and applied electric fields are m… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
48
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 35 publications
(60 citation statements)
references
References 38 publications
11
48
1
Order By: Relevance
“…In case of single crystals with topologically protected domain patterns 34 , it was reported that domains of the preferential polarization state expand while that for the opposite polarization state shrink 34,35 , highlighting the important role played by the domain walls during electrical polarization reversal. This scenario was essentially verified by Ruff et al who found that the βexponent value in their h-ErMnO3 single crystals matched very well with proper ferroelectrics undergoing polarization reversal purely through domain wall motion 9 . However, the situation might be drastically different in thin films with a high percentage of defects and/or small grain size.…”
Section: Resultssupporting
confidence: 53%
See 1 more Smart Citation
“…In case of single crystals with topologically protected domain patterns 34 , it was reported that domains of the preferential polarization state expand while that for the opposite polarization state shrink 34,35 , highlighting the important role played by the domain walls during electrical polarization reversal. This scenario was essentially verified by Ruff et al who found that the βexponent value in their h-ErMnO3 single crystals matched very well with proper ferroelectrics undergoing polarization reversal purely through domain wall motion 9 . However, the situation might be drastically different in thin films with a high percentage of defects and/or small grain size.…”
Section: Resultssupporting
confidence: 53%
“…However, although the electrostatic effects may not quench the primary structural distortion, their effects on the spontaneous polarization have not been properly addressed. In addition, an understanding of the polarization switching mechanism is of vital importance for any technological applications 9,10 . The difficulty in growth and electrical characterization of ultrathin films on structurally mismatched substrates, coupled with the intertwined interfacial and electrostatic effects, might have contributed to the lack of systematic studies in this regard.…”
Section: Introductionmentioning
confidence: 99%
“…Propelled by this observation as well as the significantly different exponent in the frequency dispersion of the coercive field compared to single crystals of the sister compound, ErMnO 3 (0.66 for epitaxial LuFeO 3 thin films versus ≈0.10 for the single crystal of ErMnO 3 ), [ 33 ] we proceeded to study the thickness dependence of this frequency dispersion. We note that practical limitations in the synthesis of thin films (i.e., extended growth times of over a few hours) limited us to thicknesses of up to 300 nm.…”
Section: Figurementioning
confidence: 99%
“…The implementation of the existing reconfigurable polarization converters can be divided into two methods. One method is to change the dielectric materials [16][17][18][19][20][21], the other is to change effective metal structure by using electronic devices [22][23][24][25][26][27][28][29][30][31][32][33]. The former method uses materials such as liquid crystals [16], graphene [17], [18], metal fluid [19], [20], vanadium oxide (VO 2 ) film [21] to replace the traditional metal and dielectric materials, this method has the characteristics of high frequency band and difficult fabrication.…”
Section: Introductionmentioning
confidence: 99%
“…One method is to change the dielectric materials [16][17][18][19][20][21], the other is to change effective metal structure by using electronic devices [22][23][24][25][26][27][28][29][30][31][32][33]. The former method uses materials such as liquid crystals [16], graphene [17], [18], metal fluid [19], [20], vanadium oxide (VO 2 ) film [21] to replace the traditional metal and dielectric materials, this method has the characteristics of high frequency band and difficult fabrication. In contrast, the latter method uses PIN diodes [22][23][24][25][26][27], varactor diode [28], [29] and MEMS switch [30], [31] which have the characteristics of easy fabrication, good electronic control performance, flexible structure and high efficiency.…”
Section: Introductionmentioning
confidence: 99%